2019
DOI: 10.3897/neobiota.44.33771
|View full text |Cite
|
Sign up to set email alerts
|

The dark side of facilitation: native shrubs facilitate exotic annuals more strongly than native annuals

Abstract: Positive interactions enhance biodiversity and ecosystem function, but can also exacerbate biological invasions. Facilitation of exotic invaders by exotic foundation species (invasional meltdown) has been studied extensively, but facilitation of exotic invaders by native foundation species has attracted less attention. Specifically, very few studies have examined the extent that native foundation species facilitate native and exotic competitors. Understanding the processes that mediate interactions between nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 95 publications
(135 reference statements)
3
48
0
Order By: Relevance
“…Most empirical studies of plant invasions have focused on negative interactions, that is competition and predation (reviewed by Jeschke et al, 2012;Maron & Vila, 2001;Mitchell et al, 2006;Roy, Lawson Handley, Schonrogge, Poland, & Purse, 2011), but positive interactions can also influence invasion trajectories (reviewed by Simberloff, 2006;Travaset & Richardson, 2014). In this context, native species in deserts can exacerbate plant invasions by strongly facilitating the abundance (Lucero et al, 2019;Schafer et al, 2012), performance (Holzapfel & Mahall, 1999) and population growth (Griffith, 2010) of invasive plant species, or by indirectly increasing the competitive effects of invasive species on native neighbours (Llambi, Hupp, Saez, & Callaway, 2018;Reisner, Doescher, & Pyke, 2015). There is some evidence that the intensity of positive interactions between native and invasive species can vary along environmental gradients (Badano, Villarroel, Bustamante, Marquet, & Cavieres, 2007;Saccone, Pages, Griel, & Michalet, 2010), but very few dryland studies have measured the intensity and importance of such interactions along an aridity gradient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most empirical studies of plant invasions have focused on negative interactions, that is competition and predation (reviewed by Jeschke et al, 2012;Maron & Vila, 2001;Mitchell et al, 2006;Roy, Lawson Handley, Schonrogge, Poland, & Purse, 2011), but positive interactions can also influence invasion trajectories (reviewed by Simberloff, 2006;Travaset & Richardson, 2014). In this context, native species in deserts can exacerbate plant invasions by strongly facilitating the abundance (Lucero et al, 2019;Schafer et al, 2012), performance (Holzapfel & Mahall, 1999) and population growth (Griffith, 2010) of invasive plant species, or by indirectly increasing the competitive effects of invasive species on native neighbours (Llambi, Hupp, Saez, & Callaway, 2018;Reisner, Doescher, & Pyke, 2015). There is some evidence that the intensity of positive interactions between native and invasive species can vary along environmental gradients (Badano, Villarroel, Bustamante, Marquet, & Cavieres, 2007;Saccone, Pages, Griel, & Michalet, 2010), but very few dryland studies have measured the intensity and importance of such interactions along an aridity gradient.…”
Section: Introductionmentioning
confidence: 99%
“…In changing drylands, positive interactions can benefit exotic plant species more than their native competitors (Abella & Chiquione, 2018). For instance, Lucero et al (2019) monitored associations between native shrubs and the annual plant communityincluding native and exotic taxa-over three years in a California desert and found that shrubs facilitated the abundance of exotic annual species 2.75 times stronger than native annual species.…”
Section: Introductionmentioning
confidence: 99%
“…At Carrizo National Monument, California, USA (35.1914°N, 119.7929°W) within the San Joaquin Desert 31 , a 5 km 2 was identified for ecological research. This site was comprised of a foundation shrub species Mormon tea, Ephedra californica 15,32,33 , other mixed annual and perennial vegetation 34 , and was occupied by the blunt-nosed leopard lizard, Gambelia sila 5,15 . For three years from 2016-2018, up to 30 individual lizards were tracked using telemetry each summer when this species was primarily active 15 .…”
mentioning
confidence: 99%
“…However, these traits that make E. californica beneficial to ecosystems through heterogeneity may also support the facilitation of invasive species. The invasive Bromus grass forms thick monocultures and preferentially establishes underneath E. californica shrubs (Lucero et al 2019). Our results suggest that the net balance of shrub effects on arthropod abundance is neutral due the strong facilitation of ground cover.…”
Section: Discussionmentioning
confidence: 71%